Conflict Resolution Efforts Linked to the Principle of Legal Certainty - Umar, Mohamad Gusnal; Mohamad Kasim, Nur; Mustika, Waode (Universitas Negeri Gorontalo, 2025)
The social conflict in Pohuwato Regency, involving local communities and mining companies, reflects the tensions between formal law and customary values. This conflict is triggered by power imbalances, a lack of recognition for customary rights, and minimal transparency in natural resource management. This study aims to analyze the root causes of the conflict, evaluate the role of law in creating social justice, and identify solutions based on the principle of inclusive legal certainty. The research methodology employs a qualitative approach with data collection techniques including interviews, observations, and document analysis. The study's findings indicate that formal law often overlooks local norms, thereby exacerbating tensions between the community and companies. Resolving the conflict requires the integration of customary values into formal policies, transparency in mining management, and the establishment of independent mediation institutions involving all parties. Additionally, economic empowerment of the community and legal education are strategic steps to enhance the community's capacity to handle conflicts. The research recommendations include strengthening the government's role as a neutral facilitator, developing local policies based on community participation, and ensuring that companies commit to relevant social responsibility programs. In conclusion, resolving the conflict in Pohuwato can serve as a model for managing similar conflicts in other regions, while supporting social harmony and sustainable development.